Research on the Shear Performance of Concrete Beams Strengthened with Lateral External Prestressing - Zhenhua Ren; Yuzhu Wang; Wei Chen; Xiantao Zeng; Xuanming Ding (Buildings)
Urban renewal and improving the structural resilience of infrastructure are the hotspots of attention in all walks of life. The structural resilience of existing infrastructure and engineering structures is deteriorating with the increase in service life. In order to quickly improve the structural resilience and service life of existing engineering structures, a new method of rapid reinforcement for in-service concrete beams is proposed in this paper, which is the external prestressed reinforcement method of the side façade. The specific procedure involves creating a penetration hole at each end of the side surface of the concrete beam, inserting a prestressed support rod into the hole and subsequently installing a prestressed long bolt within the support rod. External prestress is applied to the side façade of the concrete beam through prestressed bolts. A total of 21 reinforced concrete beams were designed and manufactured, including 3 contrast beams of ordinary concrete, 9 concrete beams reinforced with traditional external prestressing steel and 9 concrete beams reinforced with externally prestressed steel on side façades. Different initial prestressing forces were applied to the reinforced beams, and flexural shear tests and numerical analyses were carried out on the concrete beams. The failure modes and shear resistances were analyzed. This research demonstrates that, in comparison with the control beam, the ultimate bearing capacity of the traditionally externally prestressed concrete beams increased by 137.8% to 140.8%, depending on the initial prestress difference. For the externally prestressed concrete beams applied to the side façade, these increases range from 42.6% to 52.0%. Furthermore, the cracking load and yield load of the reinforced concrete beams are significantly enhanced, thereby improving their operational performance. Additionally, the numerical results confirm that the theoretical calculations align well with the experimental findings.